Implementasi Budikdamber Sebagai Upaya Pemberdayaan Ekonomi Keluarga Di Kampung Situpete, Kota Bogor - Mujito, Mujito; Tika Kartika Asri; Tyara Poernomo Putri; Mimin Rukmini; Zairin, Zairin; Jarot Wuryanto; Didin Samsudin; Siana Ria (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The community service program through the implementation of Fish Farming in Buckets (Budikdamber) was carried out in Situpete Village, Sukadamai, Tanah Sareal, Bogor City, aiming to enhance food security and empower family-based economies. The participatory method involved several stages, including field surveys, socialization, hands-on training, mentoring, and evaluation. The results showed that the community successfully mastered the basic techniques of Budikdamber, producing catfish and water spinach harvests within a relatively short period. This program not only contributed to household food security but also opened opportunities for micro-home businesses. Key success factors included strong community participation, support from neighborhood leaders, and the active role of Karang Taruna as youth mobilizers. Challenges faced were limited initial capital, water quality maintenance, and restricted space in densely populated areas. With continuous mentoring and support from local government and universities, Budikdamber has the potential to become a sustainable community empowerment model.